2015
DOI: 10.1080/1357650x.2015.1046881
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the leftward cradling bias among typically developing adults high on autistic traits

Abstract: The leftward cradling bias is the tendency to cradle infants on the left side of the body and it has been linked with hemispheric asymmetry for emotional processing. This study examines this phenomenon using a real-size infant doll in typically developing adults who score high in the Reading the Mind in the Eyes, the Autistic Spectrum Quotient and the Empathy Quotient, measures that assess autistic traits among typically developing individuals. Results revealed that this group showed a reduced tendency to crad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Studies in WEIRD (Western, Educated, Industrialised, Rich, Democratic) settings report that 65% or more mothers cradle their infants on the left side (Sieratzki & Woll, 1996). A consistent left cradling bias has also been reported from non-WEIRD settings (Fleva & Khan, 2015). For example 76% of Yanomamo (Amazonian Indian tribe) women cradled on the left (Bolton, 1978) and in a South African study, almost 90% of women in Black, Coloured and Indian samples cradled on the left (Saling & Cooke, 1978).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Studies in WEIRD (Western, Educated, Industrialised, Rich, Democratic) settings report that 65% or more mothers cradle their infants on the left side (Sieratzki & Woll, 1996). A consistent left cradling bias has also been reported from non-WEIRD settings (Fleva & Khan, 2015). For example 76% of Yanomamo (Amazonian Indian tribe) women cradled on the left (Bolton, 1978) and in a South African study, almost 90% of women in Black, Coloured and Indian samples cradled on the left (Saling & Cooke, 1978).…”
Section: Introductionmentioning
confidence: 80%
“…The link between left cradling and emotional processing is strengthened by several studies showing reduced left bias in women experiencing emotional difficulties. In the last month of pregnancy, women who cradle on the left reported being more prepared for their motherhood and had a more positive body image compered to right cradlers (Fleva & Khan, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results indicated a strong leftward cradling bias in all groups and, the authors noted, the bias appeared even stronger in individuals who were deaf [41]. The leftward cradling tendency was the subject of an experiment by Fleva and Khan [42] who observed cradling behaviours in typically developing adults on the autism spectrum. Of interest was the observation that individuals who were found to be higher functioning (milder autistic symptomology) tended to cradle a life-size doll to the left.…”
Section: Cradling Bias Of Atypical Populationsmentioning
confidence: 97%
“…Individuals exhibiting significantly more characteristics of autism tended to cradle the doll to the right. The authors concluded that the data indirectly hinted at a relationship between leftward cradling bias and brain lateralization of emotional processing [42]. Pilleggi et al [43] theorized that occurrence of leftward cradling bias was facilitated by social-affective attachment processes in neurotypical mothers.…”
Section: Cradling Bias Of Atypical Populationsmentioning
confidence: 99%